2021
DOI: 10.1002/mame.202000685
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Bridging during Melt Electrowriting of Poly(ε‐Caprolactone) and the Influence of Fiber Diameter and Wall Height

Abstract: Melt electrowriting (MEW) is a direct‐writing technology for small diameter fibers; however, due to electrostatic attraction, the technique is restricted in how close these microfibers can be positioned on the collector. Here, the minimum interfiber distance between parallel poly(ε‐caprolactone) MEW microfibers is determined for different fiber diameters and number of layers on noncoated and star‐shaped poly(ethylene oxide‐stat‐propylene oxide) (sP(EO‐stat‐PO))‐coated glass coverslips. The effect of the fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…To improve mechanical properties, the inter fibre spacing could be decreased to increase the overall fibrous content and cell infiltration and migration should then be re-evaluated. A recent study on the limits of inter fibre distances in MEW-based scaffolds reported around 60 µm inter fibre distances, which shows feasibility of decreasing fibre distances [ 29 ]. Recently, possibilities in scaffold design are increasing by the fabrication of out-of-plane fibres [ 30 ], incorporated spanning fibre sheets [ 31 ], and micro-scale layer shifting [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To improve mechanical properties, the inter fibre spacing could be decreased to increase the overall fibrous content and cell infiltration and migration should then be re-evaluated. A recent study on the limits of inter fibre distances in MEW-based scaffolds reported around 60 µm inter fibre distances, which shows feasibility of decreasing fibre distances [ 29 ]. Recently, possibilities in scaffold design are increasing by the fabrication of out-of-plane fibres [ 30 ], incorporated spanning fibre sheets [ 31 ], and micro-scale layer shifting [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this comparison, a difference is observed between the mean value of the measured inter-fiber distance with the theoretical value delineated by the red solid lines, which may be attributed to the mechanical errors of the translational stage and the complex effects of the entrapped charges remaining in the scaffold. 34 In this study, the PCL fiber deviation phenomena are quantified using an inter-fiber distance metric to evaluate the printing accuracy to some extent, but may not be applicable under all conditions. Specifically, although the inter-fiber distance is implemented herein as a surrogate for printing accuracy, there is still a need to propose a more generalizable metric that captures the various factors, such as layer number and inter-fiber distance, that cause deterioration in the printing accuracy.…”
Section: Fabrication Of Heterogeneous Scaffoldsmentioning
confidence: 99%
“…Increasing the collector speed beyond the CTS increases the lag of the jet, as observed for copolymer 1 and 2 in Figure 3A,B, and affects the accuracy of the printed constructs. [35,36] For copolymer 4, the jet speed is slightly faster than the collector speed and a pronounced heel appears, where the jet moves ahead of the nozzle (black arrow; Figure 3D).…”
Section: Mew Processingmentioning
confidence: 99%